El aporte del documental como género periodístico al emprendimiento y sostenibilidad de las personas con discapacidad: http://repositorio.ulvr.edu.ec/handle/44000/4042 - López Cedeño, Karla (2020)
This research work that addresses entrepreneurship and people with disabilities, aims to assess the contribution of this segment of the population to society and promote their inclusion in the labor market, in compliance with the principle of social cohesion and full exercise from the human rights. Through the production of the documentary Emprender sin Límites,that exposes the cases of two men who have quadriplegia, it seeks to motivate and create awareness of the role that characters can play in the areaof system and technology, as well as in optometry. The research, whose approach is qualitative is the result of a bibliographic review of scientific bases and, through the logical deductive method, the path was drawn to interrelate concepts, cases, legal and theoretical framework, with the aim of deepening the study. For the development of the present work,the empirical method was necessary; also the technique of the interview and the descriptive and documentary resources.